Analisis Framing Pemberitaan Kasus Ujaran Kebencian Dalam Kolom Komentar Akun Instagram Dan Tiktok Teuku Ryan - Arfian Suryasuciramdhan; Intan Widiyanti; Nova Nazwa Ramadhanti; Suheti Suheti (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Hate speech is an expression or opinion expressed to attack an individual or group. In the era of globalization, technological developments have advanced so much that it is easy for any group in society to access social media, for example Instagram and Tiktok, easily and freely. The results of the analysis show that there are various kinds of speech acts, including expressive and directive speech. The comments given by netizens show that they can give their opinions freely regarding Teuku Ryan's Instagram or Tiktok account. The hate speech contained in the comments column includes insults, provocations and blasphemy. This shows that the use of hate speech language is often used by netizens in the comments column and the use is considered normal because it expresses opinions. So it is recommended that public figures should be more careful in sharing or conveying something and avoid anything that is controversial, because as a public figure, their behavior will definitely attract the attention of many people.